Gastric Cancer as Preventable Disease - Rugge, Massimo; Genta, Robert M.; Di Mario, Francesco; El-Omar, Emad M.; El-Serag, Hashem B.; Fassan, Matteo; Hunt, Richard H.; Kuipers, Ernst J.; Malfertheiner, Peter; Sugano, Kentaro; Graham, David Y. (Clinical gastroenterology and hepatology, 2017)
Gastric cancer, 1 of the 5 most common causes of cancer death, is associated with a 5-year overall survival rate less than 30%. A minority of cancers occurs as part of syndromic diseases; more than 90% of adenocarcinomas are considered as the ultimate consequence of a longstanding mucosal inflammation. Helicobacter pylori infection is the leading etiology of non–self-limiting gastritis, which may result in atrophy of the gastric mucosa and impaired acid secretion. Gastric atrophy establishes a field of cancerization prone to further molecular and phenotypic changes, possibly resulting in cancer growth. This well-understood natural history provides the clinicopathologic rationale for primary and secondary cancer prevention strategies. A large body of evidence demonstrates that combined primary (H pylori eradication) and secondary (mainly endoscopy) prevention efforts may prevent or limit the progression of gastric oncogenesis. This approach, which is tailored to different country-specific gastric cancer incidence, socioeconomic, and cultural factors, requires that the complementary competences of gastroenterologists, oncologists, and pathologists be amalgamated into a common strategy of health policy.